Atomic force microscopy of DNA and bacteriophage in air, water and propanol: the role of adhesion forces. - Lyubchenko, Y L (1993)
We have developed a chemical treatment for the mica surface which allows biopolymers to be held in place for atomic force microscopy, even under water, using conventional, untreated force sensing tips. We illustrate the procedure with images of lambda DNA and fd phage. The phage adheres well enough to permit in situ imaging of the adsorption process in water. These experiments yield a mean length for the phage of 883 +/- 72 nm. This compares with a measured length of 883 +/- 33 nm when the phage are imaged after drying following adsorption from water, showing that the effect of dehydration is quite small. Adhesion forces between the force sensing tip and the substrate and the sensing tip and the biomolecules are very different in the three media (air, water and propanol). The apparent height of the phage and the width and height of the DNA depends upon these adhesion forces quite strongly. In contrast, changing the Hookean spring force exerted by the scanning tip makes little difference. These results suggest that the chemical factors involved in adhesion can dominate atomic force images and that the composition of the scanning tip is at least as important a factor as its geometry.